Back Cover: Sanitizing agents for virus inactivation and disinfection (View 2/2020). Issue 2 (26th June 2020) - Lin, Qianyu; Lim, Jason Y. C.; Xue, Kun; Yew, Pek Yin Michelle; Owh, Cally; Chee, Pei Lin; Loh, Xian Jun
Abstract : In article number 16, Xian Jun Loh, Jason Y.C. Lim and co‐workers demonstrate that virus pandemics are recurrent in human history, and one of the major means of human‐to‐human viral transmissions occur through contact with contaminated surfaces. Herein, they provide a summary of the major commercially‐available sanitising agents used to inactivate viruses and critically evaluate their effectiveness to do so. This cover art shows the use of a typical sanitizer and how the contact of the sanitizers with a virus destroys it.